Is Marketing Education Driving or Drifting? - Luck, David J. (Journal of Marketing, 1965)
“Because of its fundamental and continuing interest in marketing education, the Marketing Science Institute has completed a factual study of trends in marketing course offerings and enrollments in the member schools of the American Association of Collegiate Schools of Business. “Although the accompanying background study raises many questions, it does provide a foundation for identification and discussion of some major issues. The full report of the findings of MSI's study is available from the Marketing Science Institute, 3625 Walnut Street, Philadelphia 4, Pennsylvania.” (Wendell R. Smith, Pres., Marketing Science Institute)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDIyMjQyOTY1MDI5MDAyMDY